2021
DOI: 10.3389/fphys.2020.608788
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Processes Underlying the High Prevalence of Deep Vein Thrombosis in Critically Ill COVID-19 Patients

Abstract: Coronavirus disease 2019 (COVID-19) predisposes to deep vein thrombosis (DVT) and pulmonary embolism (PE) particularly in mechanically ventilated adults with severe pneumonia. The extremely high prevalence of DVT in the COVID-19 patients hospitalized in the intensive care unit (ICU) has been established between 25 and 84% based on studies including systematic duplex ultrasound of the lower limbs when prophylactic anticoagulation was systematically administrated. DVT prevalence has been shown to be markedly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 62 publications
1
29
0
1
Order By: Relevance
“…The more severe cases usually develop bilateral interstitial pneumonia and moderate to severe hypoxemia, resulting in respiratory failure and acute respiratory distress syndrome (ARDS) (Zhou et al, 2020). Recent data show that the most serious syndrome is associated with early localized proinflammatory cytokine release (Wang et al, 2020), hypercoagulability (Middleton et al, 2020;Voicu et al, 2020), and neutrophil extracellular trap (NET) formation (Zuo et al, 2020;Busch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The more severe cases usually develop bilateral interstitial pneumonia and moderate to severe hypoxemia, resulting in respiratory failure and acute respiratory distress syndrome (ARDS) (Zhou et al, 2020). Recent data show that the most serious syndrome is associated with early localized proinflammatory cytokine release (Wang et al, 2020), hypercoagulability (Middleton et al, 2020;Voicu et al, 2020), and neutrophil extracellular trap (NET) formation (Zuo et al, 2020;Busch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the use of anticoagulation is associated with lower mortality, especially in those critically ill, but there is still no consensus regarding the optimal level of anticoagulation [ 4 , 5 , 6 ]. The survival benefit of anticoagulation supports the initial speculation that the COVID-19 induced coagulopathy is secondary to a robust inflammatory response, leading to endothelial dysfunction, and a heightened coagulopathic cascade [7] . Our patient had a huge elevation in D-dimer levels on hospital day three and developed extensive iliofemoral DVT although he was receiving thromboprophylaxis with LMWH.…”
Section: Discussionmentioning
confidence: 63%
“…Severe COVID-19 is characterized by elevation of d-dimer and marked inflammatory and prothrombotic state. Mechanical ventilation, immobilized state, venous stasis enhance the risk, thus requiring thromboprophylaxis [ 32 ]. Usage of systemic glucocorticoids increase the risk further [ 33 ].…”
Section: Discussionmentioning
confidence: 99%